2006
DOI: 10.1002/elan.200503417
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetry of Metallic Powder Suspensions on Mercury Electrodes

Abstract: Ultrafine powder samples of Cu, Fe, Ni, Mo and W were examined voltammetrically in aqueous suspensions with hanging mercury drop electrode. According to chemical interaction of the metallic powder particles with the dispersing medium the voltammetric curves either consist of a set of individual current peaks given by particulate reduction of surface oxides on impingements of particles from their suspension upon the electrode, or correspond to electroactivity of dissolved products of chemical reaction between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…This approach can be traced to the studies of Heyrovsky et al, who showed that the reduction of polydisperse ceramic semiconductor NP colloids contributed to the cyclic voltammetry of an Hg drop electrode by a summation of cathodic steps that had an onset potential dependent on the particle size. [323] It has also been demonstrated that the faradaic current at a UME performing a redox reaction decreased in discrete steps upon the addition of insulator microparticles. Schematic representation of the single NP experiment by Stimming and co-workers.…”
Section: Nanoparticle Landingsmentioning
confidence: 99%
“…This approach can be traced to the studies of Heyrovsky et al, who showed that the reduction of polydisperse ceramic semiconductor NP colloids contributed to the cyclic voltammetry of an Hg drop electrode by a summation of cathodic steps that had an onset potential dependent on the particle size. [323] It has also been demonstrated that the faradaic current at a UME performing a redox reaction decreased in discrete steps upon the addition of insulator microparticles. Schematic representation of the single NP experiment by Stimming and co-workers.…”
Section: Nanoparticle Landingsmentioning
confidence: 99%
“…145 Heyrovsky in 2006, demonstrated detection of faradaic current transients during collisions of metal colloids particles for the first time. 146 The methodology was further developed by Bard 147 and Compton 148 using two different approaches.…”
Section: Collision-based Electrochemistrymentioning
confidence: 99%
“…In our papers on the voltammetric behavior of ultrafine metallic powders [1][2][3] we have shown that different degrees of dispersion of electroactive species react at mercury electrodes in different characteristic ways. It is known that silver compounds can exist in aqueous media in various states of dispersion [4] and that they undergo complex mechanisms of particle formation [5][6][7].…”
Section: Introductionmentioning
confidence: 98%
“…Colloidal solutions of these species already show some differences from true solutions, due to different sizes and related properties of individual particles; however, their transport to and from the electrode still occurs mostly by diffusion [10]. In fine suspensions the electroactive particles, of average dimensions between about 100 nm and 1 m, move in the medium by irregular Brownian motion and generate electrolytic current by particulate mechanism due to fortuitous impingements of the particles upon the electrode [1][2][3]. The "impingement" can be either direct mechanical contact of the electrode surface by the particle in a proper orientation, or an approach of the particle to the electrode within a distance over which electron tunneling can take place.…”
Section: Introductionmentioning
confidence: 99%